Peran Pemerintah Desa dalam Menangani Pencegahan Pernikahan Usia Dini Terhadap Pengaruh Pergaulan Bebas di Kecamatan Siompu Kabupaten Buton Selatan - Wa Nur Fida; Sry Mayunita; Fitri Aisyah Rahim (JIKA (Jurnal Ilmu Komunikasi Andalan), 2022)
This study uses qualitative research with a case study approach. The purpose of this study was to see how the role of the village government in dealing with early marriage on the influence of promiscuity on Siompu Island, South Buton Regency. The results of this study indicate that the village government's first efforts included: a) increasing and raising awareness of the people of Siompu Island that the importance of the role of the village government in dealing with the problem of the influence of promiscuity which causes marriage at an early age on Simpu Island, South Buton Regency. b) Obtain factual data and documentation that the village government plays an active role in dealing with the problem of promiscuity which causes early marriage on Siompu Island, South Buton Regency. c) provide understanding to the community about the influence of promiscuity which causes marriage at an early age so that people do not underestimate and neglect their responsibilities as parents.